2003
DOI: 10.1128/jvi.77.21.11651-11660.2003
|View full text |Cite
|
Sign up to set email alerts
|

Murine Leukemia Virus Particle Assembly Quantitated by Fluorescence Microscopy: Role of Gag-Gag Interactions and Membrane Association

Abstract: In order to track the assembly of murine leukemia virus (MLV), we used fluorescence microscopy to visualize particles containing Gag molecules fused to fluorescent proteins (FPs). Gag-FP chimeras budded from cells to produce fluorescent spots, which passed through the same pore-size filters and sedimented at the same velocity as authentic MLV. N-terminal myristylation of Gag-FPs was necessary for particle formation unless wild-type Gag was coexpressed. By labeling nonmyristylated Gag with yellow FP and wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 53 publications
(20 reference statements)
2
40
0
1
Order By: Relevance
“…CA is not tolerant to large insertions, probably because of its "cage"-like structure. The constructs MA.GFP, GFP.p12, NC.GFP, and IN.GFP may serve as tools for virus trafficking studies (38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…CA is not tolerant to large insertions, probably because of its "cage"-like structure. The constructs MA.GFP, GFP.p12, NC.GFP, and IN.GFP may serve as tools for virus trafficking studies (38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…It had previously been found that when creating pseudovirus with an MLV core containing a Gag-GFP chimera with a cleavage site downstream of NC still intact (see Materials and Methods), GFP alone was predominantly cleaved from a Gag-GFP. There were only minor amounts of unprocessed Gag-GFP and of NC-GFP (Andrawiss et al, 2003). Because GFP is slightly smaller than NC-GFP, this alternate Gag-GFP chimera may be somewhat preferable for future fusion experiments.…”
Section: The Pseudoviral-cell Fusion Systemmentioning
confidence: 99%
“…The Gag-GFP chimera was constructed by inserting GFP in place of Pol, and this eliminated a viral protease cleavage site downstream of NC (Sherer et al, 2003). As a consequence, GFP was associated with NC within the virions, whereas GFP should have been unassociated if the cleavage site were still present (Andrawiss et al, 2003). HIV-1 Rev was expressed from a pCDNA3 plasmid provided by Dr. R. Doms (University of Pennsylvania, Philadelphia, PA).…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…However, several independent lines of evidence indicate that Gag-Gag interactions occur in the cytoplasm prior to reaching the plasma membrane. Complementation experiments reveal that budding can be restored when Gag mutants defective in membrane binding are coexpressed with wild-type Gag (2,4,5,35). Moreover, cytoplasmic extracts from cells expressing Gag contain higher-order Gag assembly intermediates that increase in size in a stepwise fashion, suggesting an ordered process of dimerization, oligomerization, and multimerization (29).…”
mentioning
confidence: 97%